The Role of Security in Promoting Office Health in Fasa University of Medical Sciences - Saeed Ranjbari; abolfazl Jafargholikhani; Pooneh Tabibzadeh (Fasa University of Medical Sciences, 2020)
Background & Objective: The health of administrative order in all organs is an important element to advance the goals of organs. Protection and preservation of administrative health are some of the duties of the security department. The purpose of this study was to investigate the role of the security department in maintaining administrative health from the perspective of the staff of the University of Medical Sciences. Methods: This is a cross-sectional study conducted at Fasa University of Medical Sciences. 200 employees were selected by simple random sampling. The Office Health Questionnaire and the Role of Security in Office Health were distributed among them. Data were analyzed using SPSS 25 software. Results: The mean score of office health was 137.63 35 35.65 out of 240 possible scores. Men had a better view of office health than women and medical staff had a weaker view of office health than the health and administration department. The majority of participants had a moderate to high role in maintaining administrative health. Conclusion: Participants' views on office health in the University of Medical Sciences are almost low. However, their views on the role of security in maintaining administrative health are moderate to high. It can be concluded that employees have higher expectations from the security department as the custodian of administrative health protection.